Technical report: solving temperature of microwave heating for moist foodstuffs by using decomposition method / Fatin Alia Nabihah Mohammad, Munirah Azmi and Nor Fatihah Mohd Sharipudin - Mohammad, Fatin Alia Nabihah; Azmi, Munirah; Mohd Sharipudin, Nor Fatihah (2017)
The development of science and engineering are related with the mathematics and mathematicians. This relationship especially prominent in the case of electromagnetic theory and microwave engineering. This research study about how to find a temperature profile for a moist foodstuff in a microwave heating. This temperature is derived from Lambert Law and Maxwell Equation. This research use decomposition method in order to solve the equation temperature profile which is involve orthogonal series expansion. This research show the graph of temperature profile for a moist foodstuffs based on Lambert's Law approximation which is it is a best approximation according to the other researcher.